Hybrid Carcinoma of the Larynx: A Case Report (Adenoid Cystic and Adenocarcinoma) and Review of the Literature. (4th April 2013) - Karasmanis, Ilias; Goudakos, John K.; Vital, Iosif; Zarampoukas, Thomas; Vital, Victor; Markou, Konstantinos
Abstract : Introduction . The nonsquamous carcinomas of the larynx are considered rare with the majority of malignant tumors in this area, reaching the rate of 95%, to be squamous cell neoplasms. Case Report . The case refers to a 53-year-old man that presented with symptomatology of motor nerve disease. During the evaluation of the neurologic disease, a subglottic mass of the larynx was revealed accidentally in the imaging examination. Under general anesthesia, we performed direct laryngoscopy and biopsy of the mass. The histopathologic examination revealed a hybrid carcinoma coexistence of two different carcinomas, an adenoid cystic carcinoma and an adenocarcinoma, not otherwise specified with poor differentiation. Regarding the therapeutic plan, the mass was considered inoperable due to its expansion to trachea and the patient received radiotherapy. Conclusions . Both the adenocarcinoma and adenoid cystic carcinoma are extremely rare types of malignant tumors in the larynx. The special interest of the present case is the coexistence of these two rare tumors in the same region of the larynx, being a hybrid tumor of the salivary glands in the larynx, which is the second reported case, based on our systematic literature review.